2022
DOI: 10.3390/polym14245458
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Copper Ion Adsorbed Modified Montmorillonite/Cellulose Acetate Porous Composite Fiber Membrane by Centrifugal Spinning

Abstract: The natural adsorption material montmorillonite (MMT) was selected, and cellulose acetate (CA) was used as the loading substrate to design and prepare a kind of green and environment-friendly recyclable porous composite fiber membrane with good heavy metal ion adsorption performance. Acetic acid modified montmorillonite (HCl-MMT), sodium dodecyl sulfonate modified montmorillonite (SDS-MMT), and chitosan modified montmorillonite (CTS-MMT) were prepared by inorganic modification and organic modification, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…The adsorption tests were performed by placing 100 mg of the composite membrane in an aqueous Cu 2+ solution with a concentration of 100 mg/L for 24 h at room temperature. Results showed that the composite membrane retained up to 60,272 mg of Cu 2+ per membrane when a concentration of 5% wt montmorillonite relative to the polymer content was used [104]. For increased compatibility with CA, the montmorillonite particles were initially modified with chitosan, acetic acid or sodium dodecyl sulfonates.…”
Section: Removal Of Heavy Metals From Water Using Cellulose Acetate M...mentioning
confidence: 99%
“…The adsorption tests were performed by placing 100 mg of the composite membrane in an aqueous Cu 2+ solution with a concentration of 100 mg/L for 24 h at room temperature. Results showed that the composite membrane retained up to 60,272 mg of Cu 2+ per membrane when a concentration of 5% wt montmorillonite relative to the polymer content was used [104]. For increased compatibility with CA, the montmorillonite particles were initially modified with chitosan, acetic acid or sodium dodecyl sulfonates.…”
Section: Removal Of Heavy Metals From Water Using Cellulose Acetate M...mentioning
confidence: 99%